The Influence of Digital Workload, Role Ambiguity, and Remote Work Pressure on Technostress in HR Context in Digital Technology Companies - Hartin Kurniawati; Sonya Sidjabat; Sugiarti; Tanti Widia Nurdiani; Kasinem; Emila Sholiha (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Companies that develop digital technology encounter increased human resource information system demands because their efforts to achieve digital transformation proceed, which results in employee technostress. The study investigates how digital workload together with role ambiguity and remote work pressure create technostress in HR functions at digital technology companies. The researchers used quantitative methods with explanatory research design to conduct their study. The researchers surveyed 170 Human Resources professionals through purposive sampling to collect study data. The researchers conducted data analysis through multiple linear regression after validating and assessing reliability together with testing classical assumptions. The study results demonstrated that digital workload together with role ambiguity and remote work pressure positively impacted technostress in HR settings. HR employees who work with digital technologies and remote work face increasing risks of technostress according to the study findings. The study expands existing research about technostress within digital human resource management through its theoretical contributions. The study results present management recommendations which assist organizations in developing secure and sustainable digital monitoring systems for their workplace environments.